A non-invasive strategy for suppressing asthmatic airway inflammation and remodeling: Inhalation of nebulized hypoxic hUCMSC-derived extracellular vesicles - Xu, Xiaowei; Wang, Ying; Luo, Xinkai; Gao, Xuerong; Gu, Weifeng; Ma, Yongbin; Xu, Lili; Yu, Mengzhu; Liu, Xi; Liu, Jiameng; Wang, Xuefeng; Zheng, Tingting; et al. (Frontiers in Immunology, 2023)
Mesenchymal stromal cell-derived extracellular vesicles (MSC-EVs) are extremely promising nanoscale cell-free therapeutic agents. We previously identified that intravenous administration (IV) of human umbilical cord MSC-EVs (hUCMSC-EVs), especially hypoxic hUCMSC-EVs (Hypo-EVs), could suppress allergic airway inflammation and remodeling. Here, we further investigated the therapeutic effects of Hypo-EVs administration by atomizing inhalation (INH), which is a non-invasive and efficient drug delivery method for lung diseases. We found that nebulized Hypo-EVs produced by the atomization system (medical/household air compressor and nebulizer) maintained excellent structural integrity. Nebulized Dir-labeled Hypo-EVs inhaled by mice were mainly restricted to lungs. INH administration of Hypo-EVs significantly reduced the airway inflammatory infiltration, decreased the levels of IL-4, IL-5 and IL-13 in bronchoalveolar lavage fluid (BALF), declined the content of OVA-specific IgE in serum, attenuated the goblet cell metaplasia, and the expressions of subepithelial collagen-1 and α-smooth muscle actin (α-SMA). Notably, Hypo-EV INH administration was generally more potent than Hypo-EV IV in suppressing IL-13 levels and collagen-1 and α-SMA expressions. RNA sequencing revealed that various biological processes, such as cell adhesion, innate immune response, B cell activation, and extracellular space, were associated with the activity of Hypo-EV INH against asthma mice. In addition, Hypo-EVs could load exogenous miR-146a-5p (miR-146a-5p-EVs). Furthermore, INH administration of miR-146a-5p-EVs resulted in a significantly increased expression of miR-146a-5p mostly in lungs, and offered greater protection against the OVA-induced increase in airway inflammation, subepithelial collagen accumulation and myofibroblast compared with nebulized Hypo-EVs. Overall, nebulized Hypo-EVs effectively attenuated allergic airway inflammation and remodeling, potentially creating a non-invasive route for the use of MSC-EVs in asthma treatment.